Techno-Economic Analysis of Biogas Utilization as an Alternative Fuel - Merry Indahsari Devi; Kristian Ismail; Arifin Nur (Journal of Mechatronics, Electrical Power, and Vehicular Technology, 2014)
This paper will discuss the feasibility and economic analysis of biogas energy as a supply for the diesel engine generator. The techno-economic analysis was performed by using three parameters which are Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP) as the feasibility indicators of the biogas power plant project. Calculation of substitution was obtained from the comparison between data of diesel engine using diesel fuel and dual-fuel with biogas. Economic calculations include the substitution percentage of diesel fuel by biogas for dual-fuel. Meanwhile, the calculation of savings was based on the ratio of energy content between diesel fuel and biogas. The eventual outcome is determined using economic comparison between the use of diesel fuel and dual-fuel mode. Feasibility shows that the pilot plant of 1 to 6 kWh using diesel fuel and dual-fuel are not feasible while techno-economic parameter analysis shows that NPV0, IRRMARR, while PP is undefined. The biogas power plant project is feasible in some conditions such as there is no labor cost, and 5 and 6 kWh will be feasible under the assumption that expenses for machine maintenance is eliminated. However, even when applying both conditions where biogas is feasible, diesel fuel is still not.